(untitled) (Research, Society and Development, 2022)
Objective: To demonstrate adherence to drug treatment in leprosy patients. Methodology: This is an integrative literature review, this methodology is defined as a method that allows the synthesis of knowledge and the incorporation of the applicability of results of significant studies in practice. For the elaboration of the integrative review, bibliographic survey was carried out in the following databases: Scientific Electronic Library Online (Scielo), U.S. National Library of Medicine (PUBMED) with the help of Mendeley, Ministry of Health and official statistical data. Data were collected from July to December 2021 and covered between the years 2015 to 2020. Results: After selecting the studies, according to the inclusion and exclusion criteria, 20 scientific articles were selected from the 52 found for this study and the processing of the result and discussion, although this integrative review had not restricted its scope to research carried out in Brazil, the matrix information that makes up this discussion comes from studies produced in a national scenario. Conclusion: This lack of adherence is still high and can be considered a preponderant factor for this disease still persisting in many parts of the world. This withdrawal leads to the spread of the disease, since an untreated patient is a propagator of new infections.